Critical competence and Disinformation in Communication Theory. Analysis in the programs of the Degrees in Journalism in Spain - Jurado Martin, Montserrat (Documentación de las Ciencias de la Información, 2023)
The mass media are no longer the only source of information for accessing the world around us (Vicente and López, 2021). Social networks multiply the messages that are disseminated in the communicative process and in access to content. In this context, we must reflect on the training of future professionals and the responsibility of professors to train them in competencies and values, as well as in the capacity for learning, criticism and analysis (García and García, 2009). Specifically, critical competence is essential in the training of future journalists, in order to detect information based on misinformation, manipulation, rumors, false information, etc. This paper analyzes Communication Theory subjects in Spanish journalism degrees. Using content analysis, we study the teaching guides, the mention of critical competence, the inclusion of a specific topic on Misinformation and the relationship between these concepts. The first conclusions show eminently classical subjects based on Sociology where Misinformation and critical competence are hardly represented. Therefore, in this aspect it does not respond to an education adapted to the criteria of the EHEA in terms of critical competence and the reality of the profession.
Keywords: Misinformation; Communication theory; Critical competence; Degree in Journalism; Innovative Education; content analysis